Manufacturing of Roll Conveyors: Pembuatan Roll Conveyor Manufacturing Roll Conveyors - Herwanto, Ion Sheren Dheril; Akbar, Ali (Procedia of Engineering and Life Science, 2024)
Field work practice is a form of educational and vocational implementation that is participated in by students. Practical work aims to prepare students to become productive people and can work directly in their respective fields. Students can also experience the production atmosphere and can help deal with several problems experienced by professional engineering in factories. Conveyor systems can be said to be part of the equipment mechanics that transport materials from one place to another. This system is useful when goods need to be transported and moved from one place to another. Its existence makes the process easier, faster and more comfortable. In various industries, conveyors are very important. This system is designed to withstand heavy workloads and extreme weather conditions. The ability to adjust certain angles to help move materials. Design is divided into two, namely planning and conceptualizing. Planning this research focused on designing the conveyor for the can and plastic bottle waste sorting machine, then the consumer needs for the conveyor for the can and plastic bottle waste sorting machine were arranged as follows: a) The conveyor is easy to operate. b) Does not endanger the operator. c) Easy maintenance. d) Energy efficient conveyor from carrying out practical field work at CV. According to Agung Widodo's source, it can be concluded as follows: Industrial Automation or Industrial Automation is basically technology related to the application of mechanical, electronic and computer-based information systems to operate and control production. Key words: conveyor, roll, as roll.